Effects of urban parks on residents’ expressed happiness before and during the COVID-19 pandemic - Cheng, Yingyi; Zhang, Jinguang; Wei, Wei; Zhao, Bing (Landscape and urban planning, 2021)
•Access to high green quality parks tend to improve residents’ expressed happiness.•Living environment is associated with residents’ expressed happiness.•Different types of urban parks are likely to affect residents’ expressed happiness.•Links between parks and residents’ happiness is more evident during the pandemic. The COVID-19 pandemic has impacted human health worldwide. In these unprecedented times, the benefits of urban parks for residents have gained attention. However, few studies have explored the effects of urban parks on residents’ expressed happiness from the perspective of big data, and fewer have further deciphered the disparities between residents’ expressed happiness before and during the pandemic. In this study, we explored the effects of urban parks on residents’ happiness by including nine independent factors in baseline regression models, and chose 577 urban parks in Nanjing City, China, as study sites. Around 600,000 geotagged posts crawled on Sina Weibo (Chinese Twitter) were employed to obtain residents’ expressed happiness. The results demonstrated that residents with access to urban parks with higher normalized differential vegetation index (NDVI) values are likely to be happier; and subdistrict-scale urban parks have the highest positive association with residents’ expressed happiness. The presence of water, relatively dense populations, low land surface temperatures, and a low proportion of impervious land in the living environment were significantly associated with the higher expressed happiness of residents. The research period was divided into before and during the pandemic, and we identified that the positive association between NDVI of urban parks and residents’ expressed happiness increased by one-half during the pandemic period compared to the overall results (0.372 vs. 0.255), indicating that the COVID-19 pandemic awakened Chinese residents’ longing for high “green quality” urban parks. Our findings can provide guidance and recommendations for health-oriented urban park planning and design.